Examination of Vertical Dynamics of Passenger Car with Wheel Flat Considering Suspension Parameters. (2017) - Steišūnas, Stasys; Dižo, Ján; Bureika, Gintautas; Žuraulis, Vidas
Abstract: This paper describes the analysis of the vertical dynamics of the passenger car motion considering the vertical forces of wheel/rail interaction. The aim of this study is the assessment of the smoothness of passenger car running while one wheel is with a flat. The mathematical models of wheel flat impact on the rail and entire passenger car dynamic models are defined. In order to evaluate smoothness of rail vehicle movement by computer simulation means the software package Simpack was used. In this case, the wheel-flat was modelled considering the deviation of wheel rolling radius. On the base of the theoretical analysis, the vertical accelerations of passenger car with wheel flat running on the tangent track were evaluated. The analysis of passenger carbody oscillations was performed, while the vertical damping and stiffness of the car primary/secondary suspension changed within the specified range. The values of acceleration signals were measured and clarified. Finally, basic conclusions are given.